PT. VELOX CREATIVE INDONESIA - Dedi Setiawan; Fransisca Grace; Yolanda Aditya (International Journal of Applied Business and International Management, 2018)
From time to time, transformation are always happen because it is the key of innovation. Human always changing their mindset on how make things easier, practical, and right. The same goes to the company to keep on growing. Not only to going nowhere, but they need to get out of their comfort zone to grow rapidly by introducing the company to the international world. In this era, it is not really difficult to reach internatonal market, especially exporting/internationalization service than product manufactur. Scholars highlight four features that distinguish services from manufactured goods: (1) intangibility (services are not transportable or storable), (2) inseparability (production and consumption occur simultaneously), (3) perishability (services cannot be saved but must be consumed as they are produced), and (4) heterogeneity (services are unique and difficult to standardize) (e.g., Zeithaml, Parasuraman and Berry 1985) cause of that international trade in services witnessed discernible increase in the last two decades. According to the World Trade Organization (WTO) for the year 2013 the global services exports accounted for about one-fourth of total world exports, that is, US$4.7 trillion. It is interesting to note that this growth in services trade is the reverberation of technological advancement and improvements in telecommunication infrastructure (Banga & Kumar, 2010; Saez & Goswami, 2010) By using Nusantara project, couple of Indonesian companies are already built a partnership with the groups of Indonesian or overseas college students to exporting the company on international market.